Demographic Factors Influencing the Knowledge, Attitudes and Practices of Nurses in Preventing Iv (Intravenous) Cannula-Related Infections among Nurses in Surgical Units - Jucdong, Maricar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the demographic factors influencing nurses’ knowledge, attitudes, and practices (KAP) in preventing IV cannula-related infections in surgical units of selected Rizal Provincial Hospitals, Philippines. Guided by the Knowledge, Attitudes, and Practices (KAP) Framework and supported by Reason’s Swiss Cheese Model, Bandura’s Social Cognitive Theory, and Benner’s Novice to Expert Theory, the study investigated the relationship between demographic characteristics and infection prevention behaviors among nurses. A descriptive correlational research design was employed. Respondents were selected through random sampling, and data were collected using a structured questionnaire adapted from the Peripheral Intravenous Catheter Mini Questionnaire. Descriptive and inferential statistics were used to analyze the data. The findings revealed that nurses demonstrated very high levels of knowledge, strongly positive attitudes, and very high levels of practice in preventing IV cannula-related infections. Significant relationships were found between age and knowledge, and between length of clinical experience and both knowledge and attitudes. IV-related training was significantly associated with knowledge, while sex showed no significant relationship with knowledge, attitudes, or practices. No demographic factor significantly influenced practice. Although respondents exhibited strong competencies in infection prevention, lower scores were observed in knowledge of antiseptic concentration, clinically indicated catheter removal, hand hygiene consistency, antiseptic drying time, and documentation practices. The study concludes that effective prevention of IV cannula-related infections requires both individual competence and sustained organizational support. Continuous competency-based education, regular audits, structured supervision, and reinforcement of evidence-based practices are recommended to further strengthen infection prevention performance. The study supports SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice and Strong Institutions). Its sustainability contribution lies in enhancing patient safety, healthcare quality, workforce development, and institutional capacity for infection prevention and control.
Keywords: Clinical Experience; Infection Prevention; Intravenous Cannula-Related Infections; Knowledge; Attitudes; Practices; Nurses; Peripheral Intravenous Cannula; Surgical Units